Associations between nonauditory hallucinations, dissociation, and childhood adversity in first-episode psychosis. Issue 5 (19th October 2016) - Longden, Eleanor; House, Allan O.; Waterman, Mitch G.
ABSTRACT: Although repeated associations have been found between adversity exposure (particularly exposure to childhood sexual abuse), dissociation, and auditory hallucinations in the context of psychosis, there is little comparable research examining hallucinations in other modalities. This study aimed to determine whether cumulative adversity exposure influences the likelihood of experiencing visual, tactile, olfactory, and gustatory hallucinations among psychosis patients and whether measures of dissociation are significantly associated with nonauditory hallucinations when exposure to childhood adversity and psychological distress are adjusted for. Self-report measures and a retrospective case-control design were applied to assess nonauditory hallucinations, dissociation, psychological distress, and childhood adversity exposure in a sample of first-episode psychosis patients reporting nonauditory hallucinations ( n = 36) and controls from the same clinical population without nonauditory hallucinations ( n = 31). Case participants reported higher levels of dissociation, psychological distress, and exposure to childhood rape than the control group. Dissociation remained significantly associated with nonauditory hallucinations when we adjusted for childhood sexual abuse, other types of childhood adversity, and a combined measure of emotional distress. Indication of a dose–response relationship was detected, in that total number of adversities was significantly associated with reporting more than one modality of nonauditory hallucination. Observed associations between auditory hallucinations and dissociation in psychosis may extend to other hallucination modalities. It is suggested that more research attention be paid to the etiology and impact of nonauditory hallucinations in psychosis samples.